STUDY OF DISSOLUTION FEATURES IN CARBONATE RESERVOIR IN CENTRAL LUCONIA PROVINCE, SARAWAK - Mubin, Mukhriz (2016)
Carbonate depositions can be found widely throughout the Central Luconia Province, but the identification of the carbonate features and its geomorphology were limited within industrial records. This study focus on the dissolution features in carbonate platform at Central Luconia Province. The objective of this study are to delineate the karst geomorphology and improve understanding karst network with faulting events and facies changes in the carbonate platform, as well as identifying suitable methods that can be used to highlight the carbonate features and its geomorphology. 2D karst models and 3D karst models were generated to examine the karst geomorphology and distribution of karst structures within the area. Kek Look Tong Temple, Ipoh is chosen to be analog the study to get a taste in estimating the scale of the karst features in outcrop with what could be found in seismic data. In order to understand the karst network or connection with faulting events and facies changes, stratigraphic and fault analysis were done in details. Amplitude anomaly identification method proposed by Vahrenkamp et al (2004) was taken as example in order to delineate the karst features in seismic. GeoTeric® software was used to generate seismic attributes, to aid the delineation of dissolution features in seismic. 4 horizons were picked with three main stratigraphic units. Stratigraphic units 2 and 3 consist of carbonate layers, whilst stratigraphic unit 1 is a clastic overlying the carbonate. There are 13 main faults picked in the study with majority of the karsts area associated within the faulted zone. 2D karst model was developed based on 2 inlines whilst 3D karst models were created using various attributes analysis such as Diapir, HDFD and Combo Attributes. Using 3D karst model, it is proven that karsts are mainly from within the top carbonate horizon, and not laterally distributed. The karsts are mainly isolated and shows rounded shape, perhaps with depression which can relate to doline, caving, or tower karst structures.